Performance Analysis of a Three-Blade Savonius Vertical-Axis Wind Turbine Prototype for Charging a 12 V 7 Ah Maintenance-Free Battery - Ihat Solihat; Firmansyah Firmansyah (SEAN Institute, 2026)
The increasing demand for renewable energy has encouraged the development of small-scale wind energy conversion systems for standalone electricity generation. This study evaluates the performance of a three-blade Savonius vertical-axis wind turbine prototype in charging 12 V, 7 Ah Maintenance-Free and Flooded Lead-Acid batteries. Experimental testing was conducted indoors using a blower as the wind source with three wind source distances (100 cm, 150 cm, and 200 cm), corresponding to different wind speeds. The system performance was evaluated based on wind speed, generator rotational speed, electrical current, output power, power conversion efficiency, battery charging time, and battery endurance under lamp loads of 15 W, 25 W, and 30 W. The results showed that decreasing the distance between the wind source and the turbine increased wind speed, generator rotational speed, charging current, and electrical output power while reducing the battery charging time. The highest output power was obtained at the 100 cm distance with a charging current of 3.4 A and an output power of 10.8 W. The theoretical charging time ranged from 2.0 to 2.8 h; however, the actual charging time was longer because of electrical losses, charging controller characteristics, and battery operating conditions. Battery endurance decreased as the electrical load increased, indicating that higher discharge currents accelerated battery depletion. Overall, the prototype demonstrated the feasibility of using a Savonius vertical-axis wind turbine for small-scale battery charging applications, although improvements in turbine efficiency, energy conversion, and charging system performance are required to enhance practical performance.